PERBEDAAN PERILAKU ALTRUISME DITINJAU DARI TIPE KEPRIBADIAN DAN JENIS KELAMIN PADA REMAJA SEKOLAH MENENGAH ATAS - Annisa - Fitriani; Galistara - Kusumaningrum (Psibernetika, 2020)
Altruism is a helping act carried out without coercion and without expecting compensation from the person being helped. This study aims to determine differences in altruistic behavior in terms of personality types and gender in high school adolescents. The hypothesis proposed in this study is that there are differences in altruistic behavior in terms of personality types and gender in high school adolescents. The subjects of this study were 71 students of SMA Negeri 6 Metro. This study uses two data collection methods, first, the psychological scale (altruism behavior scale) of 35 items (α = 0, 937). Second, using 60 personality test instruments (MBTI) with the number stated in the respondent's gender identity. Based on the results of the analysis that has been done, it can be taken the results of the analysis of FA = 13,433 with p = 0,000 (p <0.01) which means there are differences in altruistic behavior in terms of personality types. FB = 13, 433 with p = 0,000 (p <0.01) which means that there are differences in altruistic behavior in terms of gender. FAB = 0.024 with a value of p = 0.879 (p> 0.05) which means there is no interaction between personality type and gender on altruistic behavior.Keywords: Altruistic behavior, gender, personality typeAltruism is a helping act carried out without coercion and without expecting compensation from the person being helped. This study aims to determine differences in altruistic behavior in terms of personality types and gender in high school adolescents. The hypothesis proposed in this study is that there are differences in altruistic behavior in terms of personality types and gender in high school adolescents. The subjects of this study were 71 students of SMA Negeri 6 Metro. This study uses two data collection methods, first, the psychological scale (altruism behavior scale) of 35 items (α = 0, 937). Second, using 60 personality test instruments (MBTI) with the number stated in the respondent's gender identity. Based on the results of the analysis that has been done, it can be taken the results of the analysis of FA = 13,433 with p = 0,000 (p <0.01) which means there are differences in altruistic behavior in terms of personality types. FB = 13, 433 with p = 0,000 (p <0.01) which means that there are differences in altruistic behavior in terms of gender. FAB = 0.024 with a value of p = 0.879 (p> 0.05) which means there is no interaction between personality type and gender on altruistic behavior.Keywords: Altruistic behavior, gender, personality type